2005
DOI: 10.2337/diabetes.54.12.3474
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Insulin Signaling Defects Downstream of Phosphatidylinositol 3-Kinase at the Level of Akt Are Associated With Impaired Nonoxidative Glucose Disposal in HIV Lipodystrophy

Abstract: More than 40% of HIV-infected patients on highly active antiretroviral therapy (HAART) experience fat redistribution (lipodystrophy), a syndrome associated with insulin resistance primarily affecting insulin-stimulated nonoxidative glucose metabolism (NOGM ins ). Skeletal muscle biopsies, obtained from 18 lipodystrophic nondiabetic patients (LIPO) and 18 nondiabetic patients without lipodystrophy (NONLIPO) before and during hyperinsulinemic (40 mU ⅐ m ؊2 ⅐ min ؊1 )-euglycemic clamps, were analyzed for insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
18
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 55 publications
10
18
1
Order By: Relevance
“…2) as previously demonstrated for IRTK to IRS-1-PI3K activity [11] and for IRS-1-PI3K activity to phosphorylation of Akt1 and Akt2 [34]. Of note, the fold changes demonstrated were of similar magnitudes to those in previous studies [11,34,35]. Our results are consistent with: (1) signal Increase from basal (%) * * * Fig.…”
Section: Discussionsupporting
confidence: 82%
“…2) as previously demonstrated for IRTK to IRS-1-PI3K activity [11] and for IRS-1-PI3K activity to phosphorylation of Akt1 and Akt2 [34]. Of note, the fold changes demonstrated were of similar magnitudes to those in previous studies [11,34,35]. Our results are consistent with: (1) signal Increase from basal (%) * * * Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to the inconsistent finding of impaired insulin action on AKT phosphorylation (6,7,(11)(12)(13), this probably reflects the large heterogeneity in both type 2 diabetic and obese non-diabetic individuals combined with the relatively small sample sizes often used in such studies. However, the impaired insulin activation of GS and the lack of dephosphorylation of GS at sites 2+2a appear to be consistent findings in type 2 diabetic patients [3,7], as well as in other insulin-resistant conditions such as PCOS [9] and HIV lipodystrophy [37]. Consistently, we have demonstrated that insulin-mediated dephosphorylation of GS at sites 2 + 2a correlates significantly with insulinstimulated NOGM in a large cohort of twins [38].…”
Section: Discussionsupporting
confidence: 71%
“…Patients with HIV lipodystrophy are characterized by having decreased oxidative and nonoxidative glucose disposal (25)(26)(27). During insulin stimulation, nonoxidative glucose metabolism is thought to primarily represent muscle glycogen synthesis (49).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (27) shows that patients with HIV lipodystrophy have a decreased insulin-stimulated GS activity in skeletal muscle. This defect in insulin action is associated with reduced dephosphorylation on sites 2 ϩ 2a, 3a, and 3a ϩ b, most likely via impaired signaling at the level of glycogen synthase kinase (GSK)-3␣ Ser 21 and GSK-3␤ Ser 9 and Akt but not further upstream at the level of IRS-1-associated phosphatidylinositol-3-kinase activity (27). The present study aimed to explore the mechanisms underlying the increase in insulin sensitivity after acute suppression of lipolysis by acipimox in patients with HIV lipodystrophy and fasting hyperinsulinemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation